Niezwykły wojownik 2. Korpusu Polskiego. Niedźwiedź Wojtek - od gór Iranu do serc polskich żołnierzy = An extraordinary warrior of the 2nd Polish Corps. Bear Wojtek - from the mountain ridge of Iran to the hearts of the Polish soldiers - Andrzejczak, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents a story of Wojtek the bear, an extraordinary companion of the soldiers of the 2nd Polish Corps during World War II. Adopted by the Polish soldiers in Iran in 1942, it became not only a mascot but also an active participant in the military life and a symbol of a genuine bond and friendship between humans and animals. Raised among the soldiers of the 22nd Artillery Supply Company, Wojtek traveled with General Władysław Anders` army across the Middle East. Its involvement in the Italian Campaign, including the Battle of Monte Cassino, where it helped to carry the ammunition crates, made Wojtek a legendary figure. After the war ended, the bear was relocated to the Edinburgh Zoo, where it lived until 1963.
Keywords: Niedźwiedź Wojtek; Monte Cassino; przyjaźń; żołnierz; wojna; pomniki; Bear Wojtek; soldier; friendship; war; monument